Project-based English Learning to Increase Student’s Motivation and Learning Achievement - Suryanti Galuh Pravitasari; Teguh Susyanto; Agus Dimyati Masykur (University of Surakarta, 2024)
This quantitative experimental design research was aimed at finding out whether a projectbased English teaching and learning activity affects the student's learning outcomes and motivation. A pretest and a post-test were given to know the students' skills before and after they joined the project-based teaching and learning process. The project was in the form of asking the students to cook any food on their preference in which they had to use English before, during, and after the process. The respondents were 11 female students which were chosen by using a simple random sampling technique. The result of the research was that the six respondents stated that they strongly agreed that project-based English teaching and learning increased their learning motivation. In addition, 5 respondents stated that they agreed. Hence, no respondents said that it was not motivational. The research also showed that there was a significant increase of 13 points in the average score between the pretest and post-test results. It means the use of project-based teaching and learning activity was scientifically proven to be effective in increasing the student's learning motivation and outcome.